The Perception and Views of Photographers on Artistic Photography in Turkey (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2018)
The purposes of this study are to know generally the perception and view of photographers on artistic photography in a purposeful sample in Turkey. Participants were purposefully selected (purposive sample) from the community of photographers because it would represent diverse photographers in Turkey. The survey included 19 questions and divided into three parts. Findings of our study revealed that most of the participants were at their middle-age, male, married, university graduates, private sector employed, DSLR users, amateur/ traveling-landscape-portrait photographers, and they shoot their photos to be happy, to document anything, and for spending time (Hobby). They mainly thought that photos should be taken for documentary reasons. The creativity is mainly dependent on perspective (or photographic seeing). Good photography could be achieved with good photographic technique, a good photo is relying on the influence to the spectator, photo critics/reading should be mainly based on technique, the most influential movement is realism, artistic photography will improve, photography in future will improve, and some are participating in photographic projects. The results show that good grounds exist in Turkey to shape artistic photography for the needs of the 21st century.